The Parliamentary Genesis of the French Semi-Presidentialism against the Background of the Process of Presidentialisation of the Fifth Republic - Łukasz Jakubiak (Ksiegarnia Akademicka Publishing, 2018)
The paper deals with the dynamics of the transformation of the semi‑presidential system of government established under the constitution of the Fifth Republic of France. The author argues that the constitutional regime adopted in 1958 has been based on fundamental principles of a broadly parliamentary model (in particular, on the so‑called dualistic parliamentarianism built on the balance between the executive and the legislative). Special attention was paid to the phenomenon of presidentialisation of the French version of the aforementioned model. This process is based on two main pillars – legal and political ones – and for several decades it has led to the gradual erosion of these elements of the system of government, which have been taken directly from parliamentarianism. This has resulted, first of all, in the emergence of the French semi‑presidentialism, and then – in a significant weakening of its pro‑parliamentary components. The author points out, however, that the strictly political dimension of presidentialisation of the system of government can be quite effectively, albeit temporarily, hampered by the occurrence of cohabitation. The latter phenomenon may be treated as a ‘return to the letter of the constitution’. On the other hand, a remarkable reduction, with the use of legal instruments, in the probability of another cohabitation period is yet another aspect of the multifaceted process of presidentialisation.